العناقيد السياحية لتنمية السياحة الداخلية في الجزائر- نموذج مقترح لعنقود سياحي بولاية سكيكدة - زيرق سوسن; روابحية عيسى (جامعة الوادي University of Eloued, 2024)
تسعى هذه الدراسة إلى تسليط الضوء على مفهوم حديث متجدد في القطاع السياحي وهو العناقيد السياحية، والتي تهدف إلى تركيز الإمكانيات والجهود لتعزيز تنافسية الوجهة السياحية، وهي إحدى الحلول التي يمكن للجزائر تبنيها من أجل دعم سياحتها خاصة السياحة الداخلية، كون هذه العناقيد تعمل في الغالب في مستوى محلي. وتبين من خلال هذه الدراسة أن السياحة الداخلية هي الأساس الذي يركز عليه القطاع السياحي وأن الاهتمام بها هو ما سيدفع به قدما، واتضح أيضا أن اقتراح نموذج لعنقود سياحي في ولاية سكيكدة الغنية بالإمكانيات السياحية الطبيعية والثقافية يمكن أن يقدم دفعا قويا للسياحة فيها. This study seeks to lighten on a renewed modern concept in the tourismsectorwhichistourism clusters, which aims to focus the potentiels and efforts to enhance the competitiveness of the tourist destination, and itis one of the solutions thatAlgeriacanadopt in order to support itstourism, especiallydomestictourism, sincethese clusters workmostly in local level. It is found through this study that domestic tourism is the basis on which the tourism sector focuses and that interest in it is what will push it forward, and it was also clear that proposing a model for a tourist cluster in Skikda state rich in natural and cultural tourism potentiels can provide a strong push to the tourism in it.
Tourism Clusters for the Development of Domestic Tourism- A proposed Model for a Tourism Cluster in Skikda
Keywords: السياحة الداخلية; سكيكدة; LocalTourism; Touristic Cluster; Mode; State of Skikda